Effect of Supplementation of Exogenous Fibrolytic Enzymes in Total Mixed Ration on Rumen Fermentation Pattern in Dairy Cows - Lunagariya, P.M.; Shah, S.V.; Gupta, R.S.; Parnerkar, Subhash; Pansuriya, Hiren; Khaire, Kashmira; Patel , G.R. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The study was planned to evaluate the effect of exogenous fibrolytic enzymes (EFE) supplementation for 56 days @ 240 mg/kg total mixed ration (TMR) on rumen fermentation in dairy cows. For this six dry non-pregnant cows were assigned in each treatment with and without EFE. The rumen metabolites were evaluated on last day of experiment. About 250 ml rumen liquor was collected from each cow at pre-feeding and at 2, 4 and 6 h post-feeding. Strained Rumen Liquor (SRL) pH of cows was 6.78 and 6.70; and total volatile fatty acids (TVFAs) concentration was 8.85 and 11.22 mM/dl, respectively for cows fed TMR without enzymes (control T1) and TMR with fibrolytic enzymes (T2) with significant difference (P<0.05). The pH was lowest and TVFAs was highest at 4 h post feeding. The values for ammonia, total, non-protein, protein and soluble nitrogen concentration in SRL were 12.43 and 13.04; 95.74 and 103.74; 28.60 and 26.72; 67.15 and 77.02; and 27.15 and 29.01 mg/dl, respectively for cows fed control T1 and T2 TMR. All nitrogen fractions were within normal range and peaked at 4 h post-feeding, lowered at 6 h post-feeding and least at 8 h post-feeding. The rumen liquor total and protein nitrogen were higher (P<0.05) for cows fed exogenous fibrolytic enzymes and remained higher up to 8 hour post-feeding, indicating good fermentation activity. These results indicated better utilization of protein sources and carbohydrate release by action of fibrolytic enzymes. The study concluded that feeding exogenous fibrolytic enzymes (240 mg/kg) supplemented TMR improves rumen fermentation in dry non-pregnant Gir and crossbred dairy cows.